Surviving Vegas, a buck at a time - Porter, Lawrence; Alexander, Kim; Area 51 Film Group, LLC; Leomark Studios ([Las Vegas, Nevada] : Area 51 Film Group, LLC, 2014)
Surviving Vegas: A Buck At A Time is a documentary motion picture that follows street performers in Las Vegas, Nevada; specifically, focusing on people who dress up as various characters. The crazy and bizarre characters solicit tourists for tips in exchange for taking photos with them. --
Originally released as a motion picture in 2014.
Chuck Krueter, Gary Downe, Samantha James, Jay Johnson.
In English; closed captioning available.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed November30, 2020)
Keywords: Street entertainers -- Nevada -- Las Vegas; Biographical films; Documentary films; Internet videos; Streaming video